In-vivo impact of prodrug isosorbide-5-nicotinate-2-aspirinate on lipids and prostaglandin D2: is this a new immediate-release therapeutic option for niacin? - GILMER, JOHN FRANCIS; HARMON, SHONA; Jones, Michael (My University, 2012)
Objectives: To evaluate the pharmacokinetics and effects of the first immediate-release (IR) niacin-aspirin prodrug (ST0702) on lipid, prostaglandin and thromboxane levels in non-human primates (NHPs). Methods: We compared 28 mg/kg crystalline IR niacin, equimolar doses of crystalline IR ST0702 and control (daily oral gavage) on low density lipoprotein cholesterol (LDL-C), apolipoprotein B (ApoB) and triglycerides (Tg) in NHPs (6 per group) over 48 hours. In addition, we compared IR niacin and ST0702 effects on prostaglandin (PG)D2, ex-vivo thromboxane B2 (TXB2) levels and plasma pharmacokinetics. Results: ST0702 is metabolised in-vivo to aspirin, niacin and salicylic acid with Tmax values of 30, 45 and 95 minutes respectively using a non-compartmental model. ST0702 resulted in 38% and 40% reductions in LDL-C and ApoB levels compared to control over the 48 hour period (p = 0.027 and p = 0.012 respectively). Corresponding values were 32% and 25% for niacin (both p = NS vs control). ST0702, but not niacin, decreased Tg levels (p = 0.017 for between group difference). Post prandial glycaemia was attenuated vs baseline in the ST0702 group only. Ex-vivo serum TXB2 generation was suppressed at 15 minutes and complete suppression of TXB2 was sustained at 24 hours (p < 0.01 vs niacin). ST0702 suppressed PGD2 exposure eightfold (p = 0.012) compared to niacin over the first 24 hours Conclusions: This two-dose study in NHPs suggests that ST0702 is more effective than IR niacin on lipid profiles, while suppressing TXB2 and PGD2 increases and preventing post-prandial glycaemia. ST0702 shows promise as a new IR therapeutic option for niacin
IN_PRESS
Keywords: Pharmacology; Immediate release niacin-aspirin prodrug; low density lipoprotein cholesterol; Apolipoprotein B; Triglycerides; thromboxane; prostaglandin